Analyzing the Operation of Performance-Based Accountability Systems for Public Services - Camm, Frank (RAND Corporation, 2010)
This report describes a framework used to organize available empirical information on one form of performance-based management, a performance-based accountability system (PBAS), which identifies individuals or organizations that must change their behavior to improve an activity's performance, an incentive structure to motivate those changes, and measures tailored to inform the incentive structure.